Parametric Studies of Triangular TLP - Kurian, V.J. (ENCON 2008, 2008)
Abstract: Tension leg platform (TLP) is a type of offshore platform suitable for petroleum exploration in deepwater. The dynamic responses of TLP such as the motions and the tether tensions when it is subjected to wave forces are needed for the design and maintenance of the structure. Limiting these responses leads to better stability and safe drilling operations. In this paper, the triangular TLP has been considered as a rigid body and all the six motions as well as tether tensions have been determined. Linear Airy wave theory and Morison equation have been used for wave force calculations. Newmark Beta method of time domain analysis has been used. The response amplitude operators for the motions of a typical TLP have been studied. Also, parametric studies for triangular TLP have been made varying parameters such as water depth, pretension, wave angle and position of centre of gravity (CG). The results highlight the variation in platform responses caused by changing these parameters. Keywords: Tension Leg Platform (TLP), triangular TLP, Dynamic response, parametric study.